Correction: Corrigendum: mTORC1-independent TFEB activation via Akt inhibition promotes cellular clearance in neurodegenerative storage diseases - Michela Palmieri (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14338 (2017); Published: 6 February 2017; Updated: 13 June 2017 This Article contains errors in Figs 2 and 3, for which we apologize. In Fig. 2c, the four images were inadvertently duplicated from the images in Fig. 2b. In Fig. 3g, the image at the upper right corner, corresponding to the condition UT_ Cln3Δex7-8 was inadvertently duplicated from the image in the lower right corner of Fig.